Numerical modeling of nitrogen removal processes in biofilters with simultaneous nitritation and anammox. - Shi, Shun (Water Science and Technology)
This study developed a simple numerical model for nitrogen removal in biofilters, which was designed to enhance simultaneous nitritation and anaerobic ammonium oxidation (anammox). It is the first attempt to simulate anammox together with two-step nitrification in natural treatment systems, which may have different kinetic parameters and temperature effects from conventional bioreactors. Prediction accuracy was improved by adjusting kinetic coefficients over the startup period of the biofilters. The maximum rates of nitritation and nitrite oxidation increased linearly over time during the startup period. Simulations confirmed successful enhancement of simultaneous nitritation and anammox (SNA) in the biofilters, with anammox contributing 35% of ammonium removal. Effluent ammonium concentration was affected by influent ammonium concentration and the maximum nitritation rate, and was insensitive to the maximum nitrite oxidation rate and anammox substrate factor. Ammonium removal via SNA was likely limited by biomass of aerobic ammonia oxidizing bacteria in the biofilters. The developed model is a promising tool for studying the dynamics of nitrogen removal processes including SNA in natural treatment systems.